(untitled) (Baghdad Science Journal, 2024)
Human leukocyte antigen G (HLA-G) is a non-classical major histocompatibility complex (MHC) protein with well-known immunomodulatory characteristics. It is also believed to be an important sign of immune tolerance in cancer cells. Immune Escape. HLA-G is also associated with disease development and prognosis in cancer patients. The goal of this study was to compare soluble HLA-G (sHLA-G) levels before and after radioactive iodine therapy (RAI) by enzyme immunoassay (ELISA). Immunohistochemistry was used to examine HLA-G protein expression in thyroid tissues from patients with papillary thyroid cancer (PTC) to investigate the relationship between HLA-G expression and patients’ clinical variables. Prospective research included 138 blood samples from patients and controls, as well as 25 thyroid paraffin-embedded tissues from individuals suffering from papillary thyroid cancer (PTC) and controls. Our findings demonstrated a significant difference in the means of people who had radioactive iodine therapy against those who did not (Mean SE = 4.19 0.31, 2.216 0.08, respectively). HLA-G staining, on the other hand, was identified in tumor cells in papillary thyroid cancer, all sections were positive, strongly stained and completely membranous, indicating the presence of HLA-G protein in the tested material. These findings suggest that HLA-G may be involved in the pathogenesis of papillary thyroid cancer.